Non-Majoritarian Institutions - A Menace to Constitutional Democracy? - Stefan Voigt (University of Hamburg, Institute of Law and Economics (ILE), 2023)
Over the last couple of decades, non-majoritarian institutions (NMIs) have been introduced in many countries. Of late, they have been criticized as promoting technocracy to the detriment of democracy. A number of political scientists even argue that they would strengthen populists and be, hence, one reason for democratic backsliding. This paper does three things: It firstly briefly discusses the empirical evidence for the claim that NMIs have strengthened populists. It secondly argues that not all NMIs are born equal and therefore proposes a taxonomy enabling us to distinguish different types. And it finally discusses the question how the delegation of policy-making competence to experts can be legitimized relying on a specific version of social contract theory. To develop the argument, the interdependence cost calculus developed by Buchanan and Tullock (1962) is modified by explicitly including the respective decision-making procedure, distinguishing between direct democracy, representative democracy, and expert decision-making.
Keywords: H11; K38; P51; 330; Nonmajoritarian institutions; constitutional democracy; technocracy; independent regulatory agencies; populism; social contract theory